If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + 3y + -2x + -6 = 0 Reorder the terms: -6 + -2x + xy + 3y = 0 Solving -6 + -2x + xy + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + -2x + xy + 6 + 3y = 0 + 6 Reorder the terms: -6 + 6 + -2x + xy + 3y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2x + xy + 3y = 0 + 6 -2x + xy + 3y = 0 + 6 Combine like terms: 0 + 6 = 6 -2x + xy + 3y = 6 Add '-3y' to each side of the equation. -2x + xy + 3y + -3y = 6 + -3y Combine like terms: 3y + -3y = 0 -2x + xy + 0 = 6 + -3y -2x + xy = 6 + -3y Reorder the terms: -6 + -2x + xy + 3y = 6 + -3y + -6 + 3y Reorder the terms: -6 + -2x + xy + 3y = 6 + -6 + -3y + 3y Combine like terms: 6 + -6 = 0 -6 + -2x + xy + 3y = 0 + -3y + 3y -6 + -2x + xy + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 -6 + -2x + xy + 3y = 0 The solution to this equation could not be determined.
| 5-2x=-5x+2 | | 5r-20=3r+18 | | (28x^12y^-6z^9/14x^7y^-2z^3)^-5 | | 10x-3=y | | 9y-8=19.9 | | 15s-10=12s+14 | | 4x^2+8x-4=4x-5 | | 2(-1)+3=-4 | | 2h+3c=4.95 | | 13j+j+3j-17j+j=16 | | 8q-14=5q+10 | | 10*x^2=15*x | | 5q-2=3q+4 | | 27x+2=26x+6 | | 2+3=-4 | | x^2+19x+83=-7 | | 15y-15=12y+12 | | 5x+2x-1=4x+4x-1 | | 4h-3h=12 | | 6y-9z-18= | | 12s-20=10s+16 | | 18-z=44 | | 0+1=-4 | | 3/4w+3/4w=1+5 | | 45=-0.2x+50 | | x^2-7x-12=-2x-6 | | 4s-2s=14 | | 2(2)+0=-4 | | y=-0.2(45)+50 | | 15x+10=16x+4 | | 6x-4(7-x)=6 | | 2(2)+1=-4 |